Analisis Penerapan Aplikasi E-Commerce Untuk Meningkatkan Penjualan di PT Kreasi Nostra Mandiri (Sayurbox) - Ulfa Dian Susanti; Komarun Zaman (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe the analysis of sales revenue at PT. Nostra Mandiri creations from 2019-2022. the data used in this study are primary data and secondary data using existing data at PT. Kreasi Nostra Mandiri from 2019-2022 Data collection techniques through observation, interviews and documentation as well as triangulating data from the findings. The analytical method used is qualitative research combined with descriptive analysis. A qualitative approach is an analysis that is used without calculating numbers, but based on judgments or opinions as well as basics that can support subjective decision making. While the use of descriptive analysis aims to explore the description of the object studied empirically. So, it can be informed of the real phenomena of the object under study. The analysis technique used in this study is to present an explanation of sales revenue by implementing an e-commerce sales system. The results of the research show that the income of PT. Kreasi Nostra Mandiri can be seen from the first time it was established in 2019 where the applications that existed at that time had many limitations with minimal usage. Tools and lots of trial and error. Not as many items are being sold as are currently provided in the application, which can be seen from the slogan in 2019 of Rp. 115,383,211, in 2020 revenue of Rp. 592,135,110, in 2021 revenue of Rp. 7,686,905,515 and in 2022 revenue will increase drastically by Rp. 57,688,312,526. The company's revenue has increased after upgrading its e-commerce application in sales by adding sub-category features, banners on the front view, and additional promos from ELDP, today's special slots and promos on IGS as well as pop up notifications via gadgets, payment methods which can be cashless (e-wallet and bank transfer).